Ethnomathematics Exploration in The Architecture of Osing Traditional Houses: Revealing the Application of Mathematical Principles in Banyuwangi Culture - Istiqomah, Istiqomah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research explores the application of mathematical principles in the architecture of Osing traditional houses in Banyuwangi through an ethnomathematics approach. Ethnomathematics is a study that examines the relationship between mathematics and culture within specific communities. By exploring this connection, the research aims to uncover the application of mathematical concepts in Osing culture, particularly in the context of their traditional house architecture. The study employs an ethnographic approach, using data collection techniques such as document studies, content analysis, and semiotic analysis. The findings reveal that the architecture of Osing traditional houses is rich in mathematical elements integrated with the cultural values of the Osing community. Geometric concepts are evident in roof shapes, decorative patterns, and building structures. Proportions and measurements are considered in the design of rooms and building elements. Numerical concepts and calculations are utilized in the construction process.These findings highlight the harmonious integration of mathematical knowledge and cultural values in the architecture of Osing traditional houses, where every building element holds symbolic meanings related to the beliefs and worldview of the Osing community. This research contributes to the preservation of Banyuwangi's cultural heritage and local wisdom while enhancing appreciation for mathematics within a cultural context.